2019
DOI: 10.1177/0011128719885869
|View full text |Cite
|
Sign up to set email alerts
|

The Individual-Level Deterrent Effect of “Call-In” Meetings on Time to Re-Arrest

Abstract: Focused on deterrence popular model to address community-level violence, however little research has examined the individual-level effect of deterrent messaging on subsequent offending. To answer this question, we utilize data on 254 gang- and group-involved probationers and parolees who attended offender “call-in” meetings as part of the Detroit Ceasefire. We employ inverse-probability weighting to construct a counterfactual comparison group from a sample of gang-involved young adults who were not subject to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Person-focused approaches aim to reduce crime through targeted enforcement activities that attempt to alter prolific, repeat offenders' risk perceptions the likelihood and severity of apprehension and punishment (Braga, Weisburd, & Turchan, 2018). Project Safe Neighborhoods and Ceasefire-inspired initiatives take a "pulling levers" approach to send the message to wouldbe offenders and criminal gangs that their behavior is being closely monitored and will no longer be tolerated (Circo et al, 2020(Circo et al, , 2021Corsaro et al, 2012;McGarrell et al, 2010). The threat of severe and swift punishment is combined with providing social service opportunities to assist with the desistance process and the reduction of crime with considerable success (Braga & Weisburd, 2012;Braga et al, 2001).…”
Section: Proactive Policingmentioning
confidence: 99%
“…Person-focused approaches aim to reduce crime through targeted enforcement activities that attempt to alter prolific, repeat offenders' risk perceptions the likelihood and severity of apprehension and punishment (Braga, Weisburd, & Turchan, 2018). Project Safe Neighborhoods and Ceasefire-inspired initiatives take a "pulling levers" approach to send the message to wouldbe offenders and criminal gangs that their behavior is being closely monitored and will no longer be tolerated (Circo et al, 2020(Circo et al, , 2021Corsaro et al, 2012;McGarrell et al, 2010). The threat of severe and swift punishment is combined with providing social service opportunities to assist with the desistance process and the reduction of crime with considerable success (Braga & Weisburd, 2012;Braga et al, 2001).…”
Section: Proactive Policingmentioning
confidence: 99%
“…5. One study found GVI-focused individuals who attended a call-in notification meeting had longer times to arrest than a matched comparison group (Circo et al , 2020). …”
Section: Notesmentioning
confidence: 99%
“…Chronic, gang-involved gun offenders are identified, invited to a "call in" meeting, and warned that the criminal justice system has collaborated to increase the certainty of specific offenders being caught for future gun crimes, to act quickly against those offenses, and to drastically increase the penalty above status quo (Circo, Krupa, et al, 2019). General deterrence is engaged when the offenders are warned that gun crimes by the targeted chronic offender, as well has his or her known associates (other gang members), will result in penalties against the group, including targeted, intensive patrols following a gun crime incident.…”
Section: Fd Frameworkmentioning
confidence: 99%